(E)-3-[4-(Hexyloxy)phenyl]-1-(2-hydroxyphenyl)prop-2-en-1-on - Zainab, Ngaini; Siti Muhaini, Haris Fadzillah; Hasnain, Hussain; Ibrahim, Abdul Razak; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C21H24O3, the conformation of the enone group is s–cis. The benzene rings are inclined at an angle of 7.9 (1). The alkoxy tail is planar, with a maximum deviation from the least-squares plane of 0.009 (2) A˚ , and adopts a trans conformation throughout. An intramolecular O—HO interaction between the keto and hydroxy groups forms S(6) ring motifs. In the crystal, molecules are arranged in a head-to-tail manner down the a axis and are subsequently stacked along the b axis, forming molecular sheets parallel to the ab plane. The crystal structure is further stabilized by weak C—H interactions and short CO [3.376 (2) A˚ ] contacts.